2010
DOI: 10.1517/17425251003680791
|View full text |Cite
|
Sign up to set email alerts
|

A role for CYP in the drug–hormone crosstalk of the brain

Abstract: The drug-hormone crosstalk may be of considerable importance in the assessment of neuroactive drugs and future drug design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 110 publications
0
10
0
Order By: Relevance
“…It metabolizes therapeutically important drugs as well as drugs of abuse [31], [32]. The expression of CYP2E1 has also been reported in cultured rat [13], [33] and human brain cells [34]. The mechanism of CYP2E1 induction is complex and depends on the substrate, species, tissue, or cell type [35], [36] and in the brain regions and cell type specific expression [37].…”
Section: Introductionmentioning
confidence: 99%
“…It metabolizes therapeutically important drugs as well as drugs of abuse [31], [32]. The expression of CYP2E1 has also been reported in cultured rat [13], [33] and human brain cells [34]. The mechanism of CYP2E1 induction is complex and depends on the substrate, species, tissue, or cell type [35], [36] and in the brain regions and cell type specific expression [37].…”
Section: Introductionmentioning
confidence: 99%
“…CYP3A metabolism of both endogenous and exogenous compounds was inhibited by alcohol in human liver (Patki et al, 2004). Induction of CYP3A4 in the frontal cortex may represent a homeostatic response to alcohol inhibition of CYP3A activity, as alterations in CYP3A activity have been proposed to affect steroid-mediated signaling in the brain (Meyer and Gehlhaus, 2010). Changes in the dopaminergic system have also been linked to altered hepatic CYP3A expression in animals (Wójcikowski et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of drug-metabolizing CYPs, including CYP2B, CYP2D, CYP2E1, CYP3A, and CYP4, have been detected in the brain (Meyer and Gehlhaus, 2010;Strobel et al, 2001) and their substrates include a wide range of centrally active drugs including opiate, antipsychotic, and antidepressant medications; thus, the impact of brain CYPs may be an important determinant of drug response. Local CYPmediated metabolism of these CNS acting drugs could have a direct impact on drug efficacy and could also contribute to drug tolerance, as seen from the shifts in propofol doseresponse curve following selective brain CYP2B manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown in a human neuronal cell line that toxicity following 1-methyl-4-phenylpyridinum was increased with the inhibition of CYP2D, an enzyme that can metabolically inactive this potent neurotoxin (Mann and Tyndale, 2010). Recent findings have also suggested a role for brain CYPs in altering the drug-hormone cross-talk in the brain, and found that neuroactive drugs that induce brain CYPs are associated with alterations in the side-effect profiles of these drugs and, in some cases exacerbate, the disease condition (Meyer and Gehlhaus, 2010).…”
Section: Discussionmentioning
confidence: 99%